2017
DOI: 10.18632/oncotarget.15523
|View full text |Cite|
|
Sign up to set email alerts
|

Annexin A13 promotes tumor cell invasion in vitro and is associated with metastasis in human colorectal cancer

Abstract: PurposeAberrantly upregulated expression of selected members of annexin, a group of calcium- and membrane-binding proteins, have been found to be associated with metastasis, poor prognosis, and other clinical characteristics in colorectal cancer (CRC), the third most diagnosed cancer. However, ANXA13 (encoding protein annexin A13), the original founder gene of the annexin A family, has not been studied carefully as a potential prognostic biomarker in CRC.MethodsThe protein level of annexin A13 was determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…There are relatively few studies on other members of the Annexin family in ovarian cancer, but it has been demonstrated that they are dysregulated in other malignant tumors, such as breast cancer, gastric cancer, colorectal cancer, and pancreatic cancer [4449]. The results of our database analyses showed that the mRNA expression levels of ANXA5, ANXA6 , ANXA7 and ANXA13 were downregulated.…”
Section: Discussionmentioning
confidence: 79%
“…There are relatively few studies on other members of the Annexin family in ovarian cancer, but it has been demonstrated that they are dysregulated in other malignant tumors, such as breast cancer, gastric cancer, colorectal cancer, and pancreatic cancer [4449]. The results of our database analyses showed that the mRNA expression levels of ANXA5, ANXA6 , ANXA7 and ANXA13 were downregulated.…”
Section: Discussionmentioning
confidence: 79%
“…In lung cancer cells, ANXA2 contributed to cisplatin resistibility via JNK-p53 pathway activation [21]. In vitro, overexpression of ANXA13 facilitated colorectal cancer cell invasion [11]. As reported, ANXA13 ectopic overexpression promoted the sensitivity of breast cancer cells to therapy with rapamycin [22].…”
Section: Discussionmentioning
confidence: 66%
“…Except it, another 11 annexin family members (ANXA1-11) are found in human [10]. These 12 members are implicated in a series of cellular processes containing membrane scaffolding, cell signaling, and apoptosis [11]. ANXA13 has two isoforms (ANXA13a and ANXA13b), which were primordially found in the screening of myristoylated gutspecific genes [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it too is associated with poor overall survival and poorer progression-free survival particularly in late stage cancers. As such, Annexin A10 may be considered as a prognostic marker when present [115], similarly annexin A13 expression is associated with lymph node metastasis, however it is not associated with tumor stage or differentiation [116].…”
Section: Annexinsmentioning
confidence: 99%